Raman’s Ordeal : Executive Motivation in a Hostile Work Environment - Sar, Ashok K. (Prabandhan: Indian Journal of Management, 2018)
The case study illustrated the complexity and dynamics of a hostile work environment in a typical large-scale project in the mines and minerals sector in India, the motivations of a key executive, and the required management skills to perform in such settings. Data were collected from the affected executives and other functionaries of the company and other related persons. The names and places were changed to maintain confidentiality. The sequence of facts presented in the case study are expected to help the readers to apply motivational theories and theories concerning management skills with a view to gain richer insights into the associated concepts. The case can also be used to illustrate distinctive aspects of organizational culture, virtues, and institutional inconsistencies.